2019
DOI: 10.1074/jbc.ra119.009130
|View full text |Cite
|
Sign up to set email alerts
|

Manganese co-localizes with calcium and phosphorus in Chlamydomonas acidocalcisomes and is mobilized in manganese-deficient conditions

Abstract: Exposing cells to excess metal concentrations well beyond the cellular quota is a powerful tool for understanding the molecular mechanisms of metal homeostasis. Such improved understanding may enable bioengineering of organisms with improved nutrition and bioremediation capacity. We report here that Chlamydomonas reinhardtii can accumulate manganese (Mn) in proportion to extracellular supply, up to 30-fold greater than its typical quota and with remarkable tolerance. As visualized by X-ray fluorescence microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 78 publications
7
55
0
Order By: Relevance
“…However, very little is known about the physiological relevance of these observed variations. The number and size of polyP bodies in cyanobacterial and algal cells can vary greatly, but they generally increase under stress conditions (Stevens et al, 1985;Jensen, 1993;Docampo et al, 2010;Aksoy et al, 2014;Tsednee et al, 2019). As in other single-cell eukaryotes, the acidocalcisome membranes in C. reinhardtii harbor the VTC complex, which is responsible for the polyP polymerase and H + -PPase activities (acidocalcisome membranes also harbor a V-type ATPase driven proton pump); the H + -PPases, with homologues in three eukaryotic clades (not present in opisthokonts and Amoebozoa), are activated by pyrophosphate (Rea et al, 1992;Kim et al, 1994;Rodrigues et al, 1999;McIntosh and Vaidya, 2002;Drozdowicz et al, 2003;Au et al, 2006;Serrano et al, 2007;Hsu et al, 2009;Tsai et al, 2014;Schilling et al, 2017;Shah et al, 2017;Segami et al, 2018a;Segami et al, 2018b) and also function in acidification of the lumen of vacuoles in land plants (Venter et al, 2006;Kajander et al, 2013;Asaoka et al, 2014).…”
Section: Acidocalcisomes and The Synthesis And Storage Of Polyphosphatementioning
confidence: 99%
“…However, very little is known about the physiological relevance of these observed variations. The number and size of polyP bodies in cyanobacterial and algal cells can vary greatly, but they generally increase under stress conditions (Stevens et al, 1985;Jensen, 1993;Docampo et al, 2010;Aksoy et al, 2014;Tsednee et al, 2019). As in other single-cell eukaryotes, the acidocalcisome membranes in C. reinhardtii harbor the VTC complex, which is responsible for the polyP polymerase and H + -PPase activities (acidocalcisome membranes also harbor a V-type ATPase driven proton pump); the H + -PPases, with homologues in three eukaryotic clades (not present in opisthokonts and Amoebozoa), are activated by pyrophosphate (Rea et al, 1992;Kim et al, 1994;Rodrigues et al, 1999;McIntosh and Vaidya, 2002;Drozdowicz et al, 2003;Au et al, 2006;Serrano et al, 2007;Hsu et al, 2009;Tsai et al, 2014;Schilling et al, 2017;Shah et al, 2017;Segami et al, 2018a;Segami et al, 2018b) and also function in acidification of the lumen of vacuoles in land plants (Venter et al, 2006;Kajander et al, 2013;Asaoka et al, 2014).…”
Section: Acidocalcisomes and The Synthesis And Storage Of Polyphosphatementioning
confidence: 99%
“…Intracellular polyP aggregates were found more than a hundred years ago, and over the past three decades, many studies have shown that different organisms require polyP to cope with various stress conditions including high temperature, oxidative stress, osmotic shock, survival during stationary phase, heavy metal accumulation, and nutrient deprivation, among others (1,5,(13)(14)(15)(16)(17)(18). Moreover, polyP synthesis affects critical cellular processes, including DNA replica-tion, transcription, translation, quorum sensing, and protein folding, and is essential for normal infectivity of many parasites (1,5,(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Lon protease interacts with polyP, activating degradation of ribosomal polypeptides during amino acid starvation of Escherichia coli (21). Last, polyP can serve as a chelator of divalent cations (Ca 2+ , Fe 2+ , Cd 2+ , Mn 2+ , and Cu 2+ , among others) and control intracellular cation availability (15,27). Despite this growing number of discoveries concerning the impact of polyP on cellular processes, many with seemingly unrelated functions, we still know little about how this polymer and its dynamic synthesis and degradation help cells acclimate to stress.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a reference genome fueled a large number of deep transcriptome-sequencing studies using many different growth conditions, allowing the identification of numerous candidate genes based on expression profiles. More recently, work in the laboratory has turned to a precise accounting of all metal atoms within the cell, as well as their subcellular localization, helped by innovations in microscopy techniques (Tsednee et al, 2019;Hong-Hermesdorf et al, 2014).…”
Section: Genomics Takes Chlamydomonas Into the Futurementioning
confidence: 99%